Thrombolysis for ischaemic stroke and glioblastoma multiforme: a case report - Garcia, Ana M (BMJ Publishing Group, 2009)
OBJECTIVE: To report the uncomplicated use of systemic thrombolysis for stroke in a patient with a misdiagnosed glioblastoma multiforme mimicking brain ischaemia and to suggest that new clinical situations question the stated exclusion criteria for intravenous thrombolysis. PATIENT: A 57-year-old male presented at the emergency room with a sudden aphasia. MEASUREMENT AND MAIN RESULTS: After Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST) exclusion criteria were ruled out, intravenous alteplase was administered. The patient presented with tonic–clonic seizures 17 min after perfusion completion, requiring phenytoine administration. Additional computed tomography scan did not show haemorrhagic transformation or brain oedema. A left temporal lobe glioblastoma multiforme was diagnosed after magnetic resonance imaging and neurosurgery. The patient became asymptomatic on the seventh day. CONCLUSION: Any history of central nervous system neoplasm is considered a contraindication to thrombolysis, but the true risk of systemic thrombolysis-precipitated intracranial bleeding is unknown. Further data are needed to establish real haemorrhage risk in this clinical condition.